Zeolite Socony Mobil-Five Coating on Ti-24 Nb-4 Zr-7.9 Sn Promotes Biocompatibility and Osteogenesis In Vitro and In Vivo. - Hang, Xiaodong; Liu, Xiaohan; Hu, Ying; Jiao, Yilai; Wu, Lin (BioMed Research International, 2021)
The aim of this study was to evaluate the biocompatibility and osteogenic potential of a Zeolite Socony Mobil-5 (ZSM-5) coating on a Ti-24 Nb-4 Zr-7.9 Sn (Ti-2448) surface. ZSM-5-modified Ti-2448 (ZSM-5/Ti-2448) and Ti-2448 (control) groups were employed. The physical and chemical properties of the two types of samples were evaluated by scanning electron microscopy, Fourier-transform infrared spectroscopy, nitrogen adsorption/desorption, and contact angle methods. The surface of the ZSM-5/Ti-2448 was rougher than that of the original Ti-2448, while the contact angle of the ZSM-5/Ti-2448 was smaller than that of Ti-2448. In addition, the ZSM-5/Ti-2448 largely increased the specific surface area and introduced silanol groups. A bone-like apatite layer could be formed on the surface of ZSM-5/Ti-2448 after 14 days of incubation in a simulated body fluid. ZSM-5/Ti-2448 was not cytotoxic. The number and alkaline phosphatase (ALP) activity of osteoblasts on ZSM-5/Ti-2448 were significantly higher than those on Ti-2448 surfaces, obtained in vitro using 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide and ALP activity assays. Few inflammatory cells were observed around ZSM-5/Ti-2448 after insertion into the femurs of Japanese white rabbits after 4, 12, and 26 weeks through hematoxylin–eosin staining. The average gray scale of transforming growth factor-β1 (TGF-β1) on ZSM-5/Ti-2448 peaked earlier than that on Ti-2448, according to immunohistochemical staining. These results indicate that ZSM-5/Ti-2448 has a good biocompatibility and improved early osteogenic potential compared to a noncoated Ti-2448.